PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK KELILING KELOMPOK TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 9 PADANG - Anggriani, Gustia; Aima, Zulfitri; Pratiwi, Merina (Pendidikan Matematika, 2014)
ABSTRACTÂ The research was conducted because of less confidence of student in giving question and opinion on learning process, less of teamwork in learning and low ability in understanding of mathematical concept it was shown by learning outcome of student on eight grades Junior High School 9 Padang. This research was aimed to find out whether studentsâ understanding of mathematical concept used cooperative learning type Roving Group teachnique will be better than used conventional learning on eight grades Junior High School 9 Padang. The research was an experiment study of the subject with a random design. The population was all student in eight grades whom were registered in academic year 2013/2014. Based on analysis of data obtained by the average results of the studentsâ understanding of mathematical concept experiment class was 80.69 it was higher than the result of control class which was 58,61. Thus, it can be concluded that understanding of mathematical concept of eight grades student in Junior High School 9 Padang used cooperative learning type Roving Group technique was better than used conventional learning.